Evaluation of nanoparticle albumin-bound paclitaxel loaded macrophages for glioblastoma treatment based on a microfluidic chip - Xie, Zuorun; Ye, Junyi; Gao, Xinghua; Chen, Hang; Chen, Maosong; Lian, Jiangfang; Ma, Jingyun; Wang, Hongcai (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Glioblastoma (GBM) is a primary brain malignancy with a dismal prognosis and remains incurable at present. In this study, macrophages (MΦ) were developed to carry nanoparticle albumin-bound paclitaxel (nab-PTX) to form nab-PTX/MΦ. The aim of this study is to use a GBM-on-a-chip to evaluate the anti-GBM effects of nab-PTX/MΦ. Methods: In this study, we constructed nab-PTX/MΦ by incubating live MΦ with nab-PTX. We developed a microfluidic chip to co-culture GBM cells and human umbilical vein endothelial cells, mimicking the simplified blood-brain barrier and GBM. Using a syringe pump, we perform sustainable perfusion of nutrient media. To evaluate the anti-GBM effects nab-PTX/MΦ, we treated the GBM-on-a-chip model with nab-PTX/MΦ and investigated GBM cell proliferation, migration, and spheroid formation. Results: At the chosen concentration, nab-PTX did not significantly affect the viability, chemotaxis and migration of MΦ. The uptake of nab-PTX by MΦ occurred within 1 h of incubation and almost reached saturation at 6 h. Additionally, nab-PTX/MΦ exhibited the M1 phenotype, which inhibits tumor progression. Following phagocytosis, MΦ were able to release nab-PTX, and the release of nab-PTX by MΦ had nearly reached its limit at 48 h. Compared with control group and blank MΦ group, individual nab-PTX group and nab-PTX/MΦ group could inhibit tumor proliferation, invasion and spheroid formation. Meanwhile, the anti-GBM effect of nab-PTX/MΦ was more significant than nab-PTX. Discussion: Our findings demonstrate that nab-PTX/MΦ has a significant anti-GBM effect compared to individual nab-PTX or MΦ administration, suggesting MΦ as potential drug delivery vectors for GBM therapy. Furthermore, the developed GBM-on-a-chip model provides a potential ex vivo platform for innovative cell-based therapies and tailored therapeutic strategies for GBM.